Spatiotemporal Evolution of and Regional Differences in Consumer Disputes in the Tourism System: Empirical Evidence from the Yangtze River Economic Belt, China - Ning Wang; Gangmin Weng (Systems)
The global tourism industry is currently experiencing a significant boom, leading to increasing prosperity in the tourism economy. However, litigation disputes and conflicts between tourism consumers and operators have become more frequent, severely disrupting the smooth functioning of tourism markets. Therefore, clarifying the spatiotemporal attributes and distributional characteristics of tourism disputes in destinations holds substantial significance for destination market governance and the sustainable development of tourism systems. Taking China’s Yangtze River Economic Belt as a case study, this research employs the geographic concentration index, the gravity center model, and the Dagum Gini coefficient to analyze the spatiotemporal patterns of different types of tourism disputes and their watershed-specific variations from 2013 to 2024. The results demonstrated that tourism disputes exhibited an increase–decrease–increase inter-annual trend. The downstream basin had the most disputes, followed by the upstream and midstream ones. Areas with a high and low incidence of disputes were interspersed, with low spatial agglomeration. The gravity center was in Hubei Province. Basin differences changed in a fluctuating manner. Basin differences were large at the beginning of the study period, and thereafter the basin differences decreased in a fluctuating manner. The inter-basin differences were more significant for travel agency disputes and catering disputes. Overall, this study effectively presented the temporal distribution characteristics, spatial evolution characteristics, and basin differences in tourism disputes using mathematical statistics, geospatial analysis, and other methods.